Disseminated Mycobacterium tuberculosis infection due to interferon γ deficiency. Response to replacement therapy. Issue 1 (22nd December 2006) - Luke Seneviratne, Suranjith; Doffinger, Rainer; Macfarlane, John; Ceron-Gutierrez, L; Amel Kashipaz, M R; Robbins, A; Patel, T; Powell, P T; Kumararatne, D S; Powell, Richard J
Abstract : The case of a previously healthy HIV seronegative woman with disseminated Mycobacterium tuberculosis infection and markedly reduced interferon γ production is reported here. Complete healing of her disseminated lesions was seen only after addition of subcutaneous interferon γ to her tuberculosis treatment.